Strategi Guru Dalam Menerapkan Sikap Tanggung Jawab Peserta Didik Kelas IV A Pada Pembelajaran Pendidikan Pancasila di SDN 74 Kota Bengkulu - Yeyen Yeyen; Dini Azari; Izzati Ramadhani Herry (Yayasan Darusssalam Bengkulu, 2024)
An attitude of responsibility is an attitude that describes a person's personality which makes a person act spontaneously and is embedded within oneself. It is important to develop an attitude of responsibility as early as possible in students, because this attitude of responsibility will bring goodness to them in the future. The aim of this research is to explain how teachers' efforts through the independent learning policy in pansila education learning are able to increase attitudes of responsibility in students and the importance of having an attitude of responsibility for each individual student. The research used qualitative methods and the research subjects consisted of the principal, one civics teacher, 1 class teacher, and 25 students. Data collection techniques include observation, interviews and documentation. Data analysis uses three stages, first data reduction, data display and drawing conclusions from the data. As well as describing the supporting and inhibiting factors in implementing an attitude of responsibility through learning citizenship education for grade IV students at SDN 74, Bengkulu City.